2021
DOI: 10.1166/jbn.2021.3008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Derived Exosomes Boost the Healing of Irradiated Wound by Regulating Cell Proliferation and Ferroptosis

Abstract: Ionizing radiation (IR) therapy for malignant tumors can damage adjacent tissues, leading to severe wound complications. Plasma-derived exosome treatment has recently emerged as a safe and impactful cell-free therapy. Herein, we aimed to determine whether plasma-derived exosomes could improve the healing of post-radiation wound. Rat plasma-derived exosomes (RP-Exos) were locally injected on cutaneous wounds created on the backs of irradiated rats and boosted the healing process as well as the deposition and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Similarly, a lower level of apoptosis was observed in irradiated endothelial cells when pre-incubated with EVs from irradiated donors, suggesting an anti-apoptotic function [77]. In accordance with our findings, rat plasma-derived exosomes have also been shown to promote proliferation, migration, and cellular survival in irradiated fibroblasts, improving the healing of cutaneous post-radiation wound when locally injected [78].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a lower level of apoptosis was observed in irradiated endothelial cells when pre-incubated with EVs from irradiated donors, suggesting an anti-apoptotic function [77]. In accordance with our findings, rat plasma-derived exosomes have also been shown to promote proliferation, migration, and cellular survival in irradiated fibroblasts, improving the healing of cutaneous post-radiation wound when locally injected [78].…”
Section: Discussionsupporting
confidence: 90%
“…It promotes the formation of ferritin-containing multivesicular bodies (MVBs) and exosomes that transport iron out of the cell and thus inhibits ferroptosis ( Brown et al, 2019 ). Exosomes themselves are also proved to have some curing functions; for instance, rat plasma-derived exosomes can enhance cell proliferation and radio-resistance-related genes and yet downregulate ferroptosis in irradiated fibroblasts ( Gan et al, 2021 ).…”
Section: Exosomesmentioning
confidence: 99%
“…Local injection of rat plasma-derived exosomes (RP-Exos) into the cutaneous wounds on the backs of irradiated rats promotes ECM remodeling and collagen production. In vitro studies indicated that RP-Exos increased the expression of genes related to cell proliferation and radioresistance but downregulated the ferroptotic death pathway in irradiated fibroblasts, thereby promoting the coalescence of irradiated wounds [ 121 ]. Approaches that promote tissue repair and healing by inhibiting ferroptosis suggest that the internal connection between ferroptosis and fibrosis has broadened the diagnosis and treatment of certain diseases.…”
Section: Ferroptosis and Fibrosismentioning
confidence: 99%